2021
DOI: 10.1088/1755-1315/653/1/012134
|View full text |Cite
|
Sign up to set email alerts
|

Increased genetic variability of sugarcane through gamma ray irradiation

Abstract: To increase the genetic diversity of sugarcane can be done through induced mutation using gamma ray irradiation. This research was carried out to determine the response and radiosensitivity of calli sugarcane variety (Kidang Kencana) to gamma ray irradiation, and knowing the diversities of phenotypic mutant of sugarcane. The research was conducted at BATAN and ICECRD, from August 2012 until March 2013. This research was arranged in Completely Randomized Design with 6 doses of gamma ray irradiation (0, 10, 20, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
4
4
0
Order By: Relevance
“…Thus, calli growth might be inhibited by increasing the gamma irradiation dose. This is in line with the research reported on sugarcane [23].…”
Section: Induced Mutation Through Gamma Irradiationsupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, calli growth might be inhibited by increasing the gamma irradiation dose. This is in line with the research reported on sugarcane [23].…”
Section: Induced Mutation Through Gamma Irradiationsupporting
confidence: 93%
“…According to [26], Browning was caused by phenol oxidation following cell membrane degradation or cell disorganization This process is an indicator of the formation of quinone as a result of the enzyme activity. This result is in line with the research of [23], which stated that irradiation at high doses could cause a change in callus color from yellowish-white to blackish brown, and callus tends to decrease its ability to regenerate. According to [17], callus with brownish or darkish color showed a decrease in the regenerate ability.…”
Section: Induced Mutation Through Gamma Irradiationsupporting
confidence: 91%
See 1 more Smart Citation
“…However, this phenotype is reversible. An additional subculture period is required to move to normal morphology, as reported in previous studies (Suhesti et al, 2021(Suhesti et al, , 2020. LC 50 represents callus sensitivity, and giving a colchicine concentration of 0.0275% can cause 50% callus death.…”
Section: Mv1 Generation Plantlet Charactersmentioning
confidence: 93%
“…However, this condition is not permanent because subculture on a medium without plant growth regulators continuously will change the plantlets to normal. It occurs because of the diplontic selection, in which cell lineage with greater vigor outcompete the slower-growing lineages within or between meristems on the same plantlets (Suhesti et al, 2021).…”
Section: Mv1 Generation Plantlet Charactersmentioning
confidence: 99%